The Influence of Make A Match Method (MAAM) and Learning Motivation towards Students’ Writing Achievement on Procedure Text of the Ninth Grade of SMPN 13 Palembang - M. Sopian; Rusman Roni; Baginda Simaibang (ELTE Journal (English Languange Teaching and Education), 2018)
AbstractThis research is concerned with the influence Make a Match Method (MAAM), and learning motivation students’ writing achievement on procedure text of the ninth grade of SMPN 13 Palembang. In this study 72 students of ninth grade students of SMPN 13 Palembang in the academic year 2017/2018 as a sample. This study applied factorial research design. Data were collected by using questionnaire and test. The data were analyzed by using Paired Sample t-test, Independent Sample t-test and Two Ways Anova. The results showed that First, there was a significant difference in writingability between the student who have high learning motivation and those who have low learning motivation taught using make a match method (MAAM) of SMPN 13 Palembang. Second, there was a significant difference in writing ability between the students who have high learning motivation and those who have low learning motivation taught using grammar translation method of SMPN 13 Palembang. Third, there was a significant difference in writing ability between the students who have high learning motivation and those who have low learning motivation taught using make a match method (MAAM) and grammar translation method of SMPN 13 Palembang. Last, There were a significant effects of make a match method (MAAM) and learning motivation towards student writing achievement on procedure text of SMPN 13 Palembang. Conclusion suggests that make a match (MAAM) and learning motivationhave sigfnificant roles to improve writing achievement..Key Words: Make a match method (MAAM), Grammar Translation Method, LearningMotivation, Writing Achievement